Screening of brinjal (Solanum melongena) for resistance to major insect pests - MUKHOPADHYAY, A; MANDAL, A (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1991-92 and 1992-93 in a farmer’, field of Siliguri in the foot-hill (tarai) region to evaluate the relative degree of resistance of fered by 41 cultivars of brinjal(Solanum meloangena L.) to major insect pests. The pests studied were the brinjal Shoot-and-fruitborer (Leucinodes orbonalis Guen.), cotton leaf hopper (Amrusca higuttula bioguttula (Ishida)], cotton aphid (Aphis gossypii Glover) and the spotted leaf beetle (Epilachna vigintiopunctataÂ Fabr.). The experimental plots were left for natural infestation and data on insect population and damages were recorded at 20-day intervals throughout the period of crop growth. Although the analysis of variance showed significant differences among the genotypes screened. no variety was found resistant to any of the 4 pests. However, the relative incidence of the pests showed that ’Nishchindipur Local’,’Muktajhuri’, ’Shyamla Dhepa’, ’Navkiran’. ’Banaras Long Purple’ and ’BB 1 were tolerant to the shootborer L. orbonalis, whereas ’Shyamla Dhepa’, ’Kalo Dhepa’ lind ’Banaras Long Purple’ were tolerant In the fruitborer L. orbonulis. ’Navkiran’ showed tolerance whereas ’R 14’ was highly susceptible to all the major pests or brinjal. Hence the varieties having tolerance or even multiple resistance, viz ’Shyamla Dhepa’, ’Kalo Dhepa’. ’Improved Muktakeshi’. ’Banaras Long Purple and ’BB 1 could beused for incorporation in the breeding programme and integrated pest management